2021
DOI: 10.1039/d0ea00020e
|View full text |Cite
|
Sign up to set email alerts
|

Viscosity and liquid–liquid phase separation in healthy and stressed plant SOA

Abstract: Molecular composition, viscosity, and phase state were investigated for secondary organic aerosol derived from synthetic mixtures of volatile organic compounds representing emissions from healthy and aphid-stressed Scots pine trees.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
56
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(60 citation statements)
references
References 127 publications
4
56
0
Order By: Relevance
“…2a), but the viscosity values of the sucrose/AS/H2O particles at this OIR are approximately two orders of magnitude lower than those of sucrose/H2O particles at the same RH. In addition, the finding of gradual enhancements in the organic-rich particle is in consistent with the result of other recent viscosity studies of SOA particles (Song et al, 2015;Grayson et al, 2016;Hosny et al, 2016;Song et al, 2016a;Song et al, 2019;Gervasi et al, 2020;Maclean et al, 2021;Smith et al, 2021). The viscosities of the sucrose/AS/H2O for OIR = 4:1 corresponds to liquid for RH > ~52%, semisolid for ~18% < RH < ~50%, and semisolid or solid for RH < ~18%.…”
Section: Viscosities In Ternary Systems Of Sucrose/as/h2o With Differ...supporting
confidence: 91%
See 1 more Smart Citation
“…2a), but the viscosity values of the sucrose/AS/H2O particles at this OIR are approximately two orders of magnitude lower than those of sucrose/H2O particles at the same RH. In addition, the finding of gradual enhancements in the organic-rich particle is in consistent with the result of other recent viscosity studies of SOA particles (Song et al, 2015;Grayson et al, 2016;Hosny et al, 2016;Song et al, 2016a;Song et al, 2019;Gervasi et al, 2020;Maclean et al, 2021;Smith et al, 2021). The viscosities of the sucrose/AS/H2O for OIR = 4:1 corresponds to liquid for RH > ~52%, semisolid for ~18% < RH < ~50%, and semisolid or solid for RH < ~18%.…”
Section: Viscosities In Ternary Systems Of Sucrose/as/h2o With Differ...supporting
confidence: 91%
“…3b). Previous studies have shown such behaviour that organic-rich or SOA particles also cracked upon poking, without the appearance of crystallization (Song et al, 2019;Song et al, 2021;Smith et al, 2021). In particles consisting sucrose/AS/H2O particles with an OIR = 1:1, the mean viscosity varied from ~1 × 10 -2 to ~4 × 10 1 Pa‧s from ~70% to ~34% RH (yellow symbols in Fig.…”
Section: Viscosities In Ternary Systems Of Sucrose/as/h2o With Differ...mentioning
confidence: 84%
“…We developed a parameterization for the viscosity of simulated pine tree SOA as a function of RH and temperature using the following data: (1) measured room-temperature viscosity data of SOA generated by the photooxidation of a mixture of volatile organic compounds (VOCs) representing emissions from healthy Scots pine (Pinus sylvestris) trees and (2) room-temperature viscosity data of water . These data are shown in Figure a.…”
Section: Materials and Methodsmentioning
confidence: 99%
“…The measured viscosities for the simulated Scots pine tree SOA at RH values less than or equal to 50% were taken from Smith et al, while the measured viscosities at RHs greater than 50% are based on new measurements discussed in the Supporting Information (Sections S1 and S2). The measured viscosities from Smith et al were based on the poke-flow technique, and the new measurements reported in the Supporting Information were based on the poke-flow technique and fluorescence recovery after photobleaching (FRAP). To determine viscosities from the poke-flow measurements, we used fluid simulations, which require material properties such as surface tension and slip length as the input .…”
Section: Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation